The Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Di PT. Alam Bumi Lestari - Yudha Dwiputra Putra; Lisa Lisa; Sutarno Sutarno; Dewi Anggraini; Supriyanto Supriyanto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Product quality is an important part that must be considered in the sales process. Product quality is also an advantage of a product in meeting customer needs and desires. While the purchase decision is the attitude of consumers in determining one of several alternative choices. Quality products will greatly affect consumer purchasing decisions. Pt. Bumi Alam Lestari has 300 active customers. The formulation of the problem in this study, "Does product quality affect purchasing decisions at PT. Sustainable Natural Earth?”. The goal to be achieved in this study is to determine whether there is an effect of product quality on purchasing decisions at PT. Sustainable Natural Earth. The research method used is quantitative associative. The number of respondents / samples of 60 customers from a population of 300 customers with the sampling technique is incidental sampling. The large influence of product quality on purchasing decisions can be seen in the determination test, the percentage is 45.20% with the results of this coefficient of determination, it can be concluded that the purchasing decision of PT. Bumi Alam Lestari 45.20% is influenced by product quality, while the remaining 54.80% is contributed by other factors that can be explained by other variables outside the model.